Effect of crating density and weather conditions during transit on preslaughter losses, physiological characteristics, and meat quality in broilers - Myunghwan Yu; Elijah Ogola Oketch; Nuwan Chamara Chathuranga; Shan Randima Nawarathne; Jun Seon Hong; Venuste Maniraguha; Bernadette G. Sta. Cruz; Eunsoo Seo; Jeseok Lee; Haeeun Park; Jung Min Heo (Journal of Animal Science and Technology)
The impact of crating density and prevailing weather conditions during transit on preslaughter losses, physiological characteristics, and meat quality in broilers was investigated. A total of 900 35-day-old Ross 308 male broilers with an average body weight of 1,860 ± 17.458 g (mean ± SEM) in summer and 1,864 ± 17.454 g in winter were allotted to one of six groups arranged in a 3 × 2 factorial arrangement according to the three different crating densities (low: 0.039 m2/bird; medium: 0.031 m2/bird; high: 0.026 m2/bird) and two different weather conditions (low: −1°C and high: 30°C). Birds stocked at medium density recorded lower (p < 0.05) body weight loss compared to the low density group; and demonstrated higher (p < 0.05) lactate levels along with lower (p < 0.05) respiration rates when compared to the high crating density group. Extreme conditions of low crating density under low air temperature and high crating density under high air temperature led to higher (p < 0.001) body weight loss and glucose concentration compared to low crating density under high air temperature. In conclusion, both excessively high and low crating densities are not conducive to reducing preslaughter losses and blood stress indicators. Broiler transportation under high crating density in low air temperatures and low crating density in high air temperatures is recommended.